Revealing Puns Used in SpongeBob SquarePants Animated Show - Primanda, Khoirur Rizky (Language Horizon: Journal of Language Studies, 2021)
Puns can be found anywhere whether it be TV shows or other media, especially the show Spongebob Squarepants. The show itself has various kinds of jokes and some of them involve some form of puns or even wordplays in general. This makes the jokes in there interesting to study to how they use the ambiguity of words as an entertainment. The study aims to find out what types of ambiguities or what types of puns that the show used. This research’s data will be in the form of dialogues that contain puns that can be found in Spongebob Squarepants animated shows, which makes this research descriptive qualitative since it is not numerical. First of all, the material that would be used as this research’s data source will be downloaded through the internet through various websites. The puns themselves are taken from the transcript of the show which also can be found on the internet. The way the research will be done is by watching the show itself and picking up the puns along the way and also understanding the context of those puns. The research found out that Spongebob Squarepants animated series only used homonymic, homophonic, paronymic, and polysemic puns, leaving out homography.